Employer as an Actor of Student-Centered Education: Implementation Experience - D. V. Dubrov; M. V. Kochetkov; V. Y. Steklyannikov (Высшее образование в России, 2020)
The methodological problem of student-centered education and the person-oriented paradigm is revealed. The article considers the experience of Norilsk State Industrial Institute on the creation of a dialogue atmosphere «teacher – student – employer», which is characterized by respectful attitude of a student towards a teacher and employer. Our approach implies that student accepts a guiding influence of teacher and employer on his/her personal and professional development. The authors dwell on the model that has been introduced in the educational process to develop hard and soft skills in students demanded by the employer. The employer compiles competency models for every training area. According to these models, the University forms competency maps. A rapid response of the university to the formation of the relevant hard and soft skills is possible due to introducing them into the system of supplementary education, as well as the active participation of the employer at all stages of the educational process. The educational program «Formation of soft skills based on the practice of mindfulness» on the portal of the Norilsk State Industrial Institute is available for free and free training for everyone.